Violation of the Hormonal Spectrum in Polycystic Ovaries in Combination with Insulin Resistance. What is the Trigger: Insulin Resistance or Polycystic Ovary Disease? - Lomteva S V; Shkurat T P; Bugrimova E S; Zolotykh O S; Alexandrova A A; Karantysh G V (مجلة بغداد للعلوم, 2022)
Polycystic ovary syndrome (PCOS) is the main cause of female infertility. The role of insulin resistance in the development of polycystic ovary is actively discussed here. The study included patients with PCOS without insulin resistance (n = 48) and with insulin resistance (n = 39). The comparison groups were patients with no history of PCOS: a control group without insulin resistance (n = 46) and a group of patients with insulin resistance (n = 45). The following parameters were determined in patients: FSH, LH, TSH, T3f, T4f, PRL, E2, 17-OHd, Pr, AMH, Test total, Testf, DHEAS, DHEASs, SHBG, ACTH, cortisol, IRI, IGF-1, C-peptide, and glucose level. The HOMA-IR index and the LH / FSH ratio and the total / SHBG test were calculated. Correlation analysis was also performed between HOMA IR and indicators of the hormonal profile, IGF-1, and C-peptide.Unidirectional changes in the levels of the following hormones were found in insulin resistance, PCOS and / or insulin resistance relative to control values: estradiol, total testosterone, cortisol, prolactin, AMG, and SHBG. As a result of the correlation analysis, negative relationships were established between the HOMA IR Index and the levels of E2, cortisol and AMH in patients (except for the control group).We assume that the formation of the phenotype of polycystic ovary with a combination of insulin resistance can be formed in patients with insulin resistance as a result of a decrease in the level of estradiol, SHBG and an increase in the content of total testosterone and AMH.